Inhibition of Lithium Sensitive Orai1/ STIM1 Expression and Store Operated Ca2+ Entry in Chorea-Acanthocytosis Neurons by NF-κB Inhibitor Wogonin - Basma Sukkar; Stefan Hauser; Lisann Pelzl; Zohreh Hosseinzadeh; Itishri Sahu; Tamer al-Maghout; Abdulla Al Mamun Bhuyan; Nefeli Zacharopoulou; Christos Stournaras; Ludger Schöls; Florian Lang (Cellular Physiology and Biochemistry, 2018)
Background/Aims: The neurodegenerative disease Chorea-Acanthocytosis (ChAc) is caused by loss-of-function-mutations of the chorein-encoding gene VPS13A. In ChAc neurons transcript levels and protein abundance of Ca2+ release activated channel moiety (CRAC) Orai1 as well as its regulator STIM1/2 are decreased, resulting in blunted store operated Ca2+-entry (SOCE) and enhanced suicidal cell death. SOCE is up-regulated and cell death decreased by lithium. The effects of lithium are paralleled by upregulation of serum & glucocorticoid inducible kinase SGK1 and abrogated by pharmacological SGK1 inhibition. In other cell types SGK1 has been shown to be partially effective by upregulation of NFκB, a transcription factor stimulating the expression of Orai1 and STIM. The present study explored whether pharmacological inhibition of NFκB interferes with Orai1/STIM1/2 expression and SOCE and their upregulation by lithium in ChAc neurons. Methods: Cortical neurons were differentiated from induced pluripotent stem cells generated from fibroblasts of ChAc patients and healthy volunteers. Orai1 and STIM1 transcript levels and protein abundance were estimated from qRT-PCR and Western blotting, respectively, cytosolic Ca2+-activity ([Ca2+]i) from Fura-2-fluorescence, SOCE from increase of [Ca2+]i following Ca2+ re-addition after Ca2+-store depletion with sarco-endoplasmatic Ca2+-ATPase inhibitor thapsigargin (1µM), as well as CRAC current utilizing whole cell patch clamp recording. Results: Orai1 and STIM1 transcript levels and protein abundance as well as SOCE and CRAC current were significantly enhanced by lithium treatment (2 mM, 24 hours). These effects were reversed by NFκB inhibitor wogonin (50 µM). Conclusion: The stimulation of expression and function of Orai1/STIM1/2 by lithium in ChAc neurons are disrupted by pharmacological NFκB inhibition.